MOCCA-SURVEY Database I: tidal disruption events of white dwarfs in globular clusters and young mass clusters - Tanikawa, Ataru; Giersz, Mirek; Arca Sedda, Manuel (Monthly notices of the Royal Astronomical Society, 2022)
We exploit more than 1000 star cluster Monte Carlo models from the mocca Survey Database I, to infer the local rate density of white dwarf (WD) tidal disruption events (TDEs) in globular clusters (GCs) and young massive clusters (YMCs). We suggest that the WD TDE rate for GCs and YMCs in the local Universe is ∼90-500 yr−1 Gpc−3, with 90 per cent of WD TDEs occurring in GCs. The total WD TDE rate density is ∼9-50 times larger than estimated previously. Our results show that thermonuclear explosions induced by WD TDEs can be observed at a rate of ∼100-550 yr−1 by the next generation optical surveys, such as the Legacy Survey of Space & Time by the Vera C. Rubin Observatory. We also find that massive WDs are preferentially disrupted as a result of mass segregation, and that 20 per cent of exploding WDs have mass$\gtrsim 1.0 \, {\rm M}_\odot$ despite the small population of such WDs.